Understanding the strengths, challenges, and opportunities within the international student life cycle - Vasandani, Minalli; Khan, Sohil; Chandgothia, Anshruta; Davey, Andrew K (Journal of International Students, 2026)
The rising number of international students in higher education offers many benefits but presents challenges to students, including adapting to independent living, academic and social acculturation, and financial pressures. These challenges can affect students’ mental health, academic engagement, and overall well-being. Despite universities offering various support services, their utilization remains inconsistent. This study explored the perspectives of academics, students, and international marketing representatives on international student experiences in health programs at an Australian university via a qualitative, two-phase approach, including focus groups and a co-design process to identify solutions. The study moved beyond traditional academic and counseling perspectives by incorporating international marketing representatives as transition brokers alongside students, alumni, and academics. Three key themes emerged: student support services, learning and teaching experiences, and employability. Strengths within these themes included assignment support, peer mentoring, and career development, whereas challenges involved access to psychosocial support, accommodation, and financial aid. Concerns about program recognition internationally and flexibility were also noted. Strengthening international partnerships was identified as a solution to these concerns. The findings highlight the importance of comprehensive support services that address academic, health, personal well-being, and employability needs throughout the student lifecycle. Importantly, both students and staff must be aware of these services and how to access them.